Media consumption of students: features and trends of transformation - Valkouski, Мikhail A. (Journal of the Belarusian State University. Journalism, 2019)
This article examines the structure of media consumption of students of Belarusian universities: the sources of news, entertainment and educational information that they use, preferences in choosing platforms, the time they spend on Internet surfing. The empirical part is based on the results of a survey of respondents. In the theoretical part, the author examines the trends in the evolution of journalism in the era of mobile Internet, the development of digital media economics and the economy of attention, based on the interests and needs of the generation of people who grew up in the conditions of active development of digital technologies.
Keywords: media; media consumption; digital economy; economics of attention